Differential effects of age, sex and dexamethasone therapy on ACE2/TMPRSS2 expression and susceptibility to SARS-CoV-2 infection - Shahbaz, Shima; Oyegbami, Olaide; Saito, Suguru; Osman, Mohammed; Sligl, Wendy; Elahi, Shokrollah (Frontiers in Immunology, 2022)
ACE2 and TMPRSS2 are crucial for SARS-CoV-2 entry into the cell. Although ACE2 facilitates viral entry, its loss leads to promoting the devastating clinical symptoms of COVID-19 disease. Thus, enhanced ACE2/TMPRSS2 expression is likely to increase predisposition of target cells to SARS-CoV-2 infection. However, little evidence existed about the biological kinetics of these two enzymes and whether dexamethasone treatment modulates their expression. Here, we show that the expression of ACE2 at the protein and mRNA levels was significantly higher in the lung and heart tissues of neonatal compared to adult mice. However, the expression of TMPRSS2 was developmentally regulated. Our results may introduce a novel concept for the reduced susceptibility of the young to COVID-19 infection. Moreover, ACE2 expression but not TMPRSS2 was upregulated in adult female lungs compared to their male counterparts. Interestingly, the ACE2 and TMPRSS2 expressions were upregulated by dexamethasone treatment in the lung and heart tissues in both neonatal and adult mice. Furthermore, our findings provide a novel mechanism for the observed differential therapeutic effects of dexamethasone in COVID-19 patients. As such, dexamethasone exhibits different therapeutic effects depending on the disease stage. This was supported by increased ACE2/TMPRSS2 expression and subsequently enhanced infection of normal human bronchial epithelial cells (NHBE) and Vero E6 cells with SARS-CoV-2 once pre-treated with dexamethasone. Therefore, our results suggest that individuals who take dexamethasone for other clinical conditions may become more prone to SARS-CoV-2 infection.